2018
DOI: 10.1111/his.13665
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular matrix components indicate remodelling activity in different fibrosis stages of human non‐alcoholic fatty liver disease

Abstract: Advanced human NAFLD-fibrosis has a distinct ECM composition with increased HSCs and increased TIMP inhibition, but there is also ongoing remodelling activity of MMP-2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 35 publications
2
26
0
Order By: Relevance
“…MMPs play a crucial role in ECM homeostasis due to HSC activation into a profibrogenic phenotype occurring during inflammation [37,38]. Recent data have shown an ongoing remodelling activity of MMP-2 in advanced human NAFLD fibrosis [39]. In the present study, we documented, for the first time, a positive correlation between desaturases, D5D, D9-16D and D19-18D, with MMP-2 protein content and its gelatinolytic activity in NAFLD animal models.…”
Section: Discussionmentioning
confidence: 99%
“…MMPs play a crucial role in ECM homeostasis due to HSC activation into a profibrogenic phenotype occurring during inflammation [37,38]. Recent data have shown an ongoing remodelling activity of MMP-2 in advanced human NAFLD fibrosis [39]. In the present study, we documented, for the first time, a positive correlation between desaturases, D5D, D9-16D and D19-18D, with MMP-2 protein content and its gelatinolytic activity in NAFLD animal models.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, to explore the relation between PR3, NE and AAT and the advanced stages of NAFLD we selected a cohort of 41 patients with biopsy-diagnosed NAFLD. Patients included in this cohort were recruited in the context of another clinical study regarding development of fibrosis in NAFLD and patients’ characteristics were previously described (Munsterman et al 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Liver lysates were prepared as previously described (Munsterman et al 2018). PR3 and NE concentrations were measured in liver lysates according to manufacter’s protocol (cat# HK384, HK319 respectively, Hycult Biotech, Uden, The Netherlands).…”
Section: Methodsmentioning
confidence: 99%
“…In accordance, Hemman et al [50] previously reported that in activated HSCs, TIMP-1 expression is increased, and concomitantly MMPs activity is reduced, leading to protein accumulation. Recently, an increase of pro-MMP-2 accompanied by increased TIMP-1 and TIMP-2 levels in NAFLD liver fibrosis [51] has been reported. In accordance, Yilmaz et al [52] described an increase of TIMP-1 serum levels in patients with significant fibrosis, and this was identified as an independent predictor of histological fibrosis.…”
Section: The Role Of Mmps In Different Tissuesmentioning
confidence: 99%